Aerodynamics behaviour of Persona car using computational fluid dynamics (CFD) - Mohd Shaifullah, Shahruddin (2009)
An aerodynamic characteristic of a car is of significant interest in reducing car accidents due to wind loading and in reducing the fuel consumption. On the limitations of conventional wind tunnel experiment and rapid developments in computer hardware, considerable efforts have been invested in the last decade to study vehicle aerodynamics computationally. This report presents a numerical simulation of flow around Proton Persona car using commercial fluid dynamics software FLUENT for 2D simulation and COSMOSFloWorks for 3D simulation. The study focuses on CFD-based lift and drag coefficient prediction on the car body and the air flow pattern around the car body using Computational Fluid Dynamics (CFD) software. A three dimensional computer model of a Proton Persona was used as the base model in this study. The wind speed selected in this study ranges from 80 km/hr to 140 km/hr with increment of 20 km/hr. After numerical iterations are completed, the aerodynamic data and detailed complicated flow behaviour are visualized clearly. The drag and lift coefficient of Proton Persona have been estimated by using a mathematical equations. The pressure and velocity distributions along the surface of the car also have been analyzed. From the results obtained, it was found that highest speed occurs where the pressure is lowest, and the lowest speed occurs where the pressure is highest. Therefore it satisfies the Bernoulli's principle. In addition, the flow pattern around the model showed very similar with the previous works, emphasizing in findings.